2018
DOI: 10.5430/cns.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between perceived educational environment and academic achievement among critical care nursing students

Abstract: Objective: The integrated nursing educational environment remains to have a crucial influence on the student achievement, behaviors, satisfaction and success. The current study aimed to explore the relationship between perceived educational environment and academic achievement among critical care student nurses. Methods: Participants of this quantitative exploratory descriptive co-relational study were 64 students selected conveniently from the students enrolled in Critical Care Nursing course at spring and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…This finding is consistent with Koirala, Koirala, and Neupane (2019) study on academic selfperception which recruited 172 Proficiency Certificate Level (PCL) nursing students at Maharajgunj, and showed that students had positive feelings toward themselves. However, the current study finding is contradicted by Shalaby and Aljezani (2018) who did not show a statistically significant relationship between students' academic achievement and their clinical and educational environment perception.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with Koirala, Koirala, and Neupane (2019) study on academic selfperception which recruited 172 Proficiency Certificate Level (PCL) nursing students at Maharajgunj, and showed that students had positive feelings toward themselves. However, the current study finding is contradicted by Shalaby and Aljezani (2018) who did not show a statistically significant relationship between students' academic achievement and their clinical and educational environment perception.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the atmosphere of the EE influences students' education knowledge and academic achievements (Erhabor & Don, 2016). Studies have shown that there is a strong association between EE and excellent students' achievement, satisfaction, and success (Shalaby & Aljezani, 2018). Studies indicate that EE is predominantly perceived as positive, but also state that improvements are mandatory to develop physical classroom climate, and the applied teaching and learning policies (Daniels & Mthimunye, 2019;Victor, Ishtiaq, & Parveen, 2016).…”
mentioning
confidence: 99%